Proccedings of International Conference "Contemporary Issues in Business, Management and Education" 2015 2015
DOI: 10.3846/cibme.2015.09
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Market Selection Methods in a Changing International Trade Environment: the Case of Lithuanian SMEs

Abstract: International business environment is changing: globalization, trade sanctions, domestic regulations, international operations across different cultures, importance of communication, demand of sustainable supply chains and other factors force companies to diversify their markets continuously, adapt foreign market development strategies and meet market requirements at a large scale. A dilemma for SMEs is obvious as the future road in foreign market selection is uncertain: global or regional approach has to be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In total 50% of each target group see that these elements create differences in attitudes but these elements are seen with the lowest impact on decision making. Brazinskas (2015) indicated that more that 60% of companies place priority on in geographic proximity situated neighboring markets;…”
mentioning
confidence: 99%
“…In total 50% of each target group see that these elements create differences in attitudes but these elements are seen with the lowest impact on decision making. Brazinskas (2015) indicated that more that 60% of companies place priority on in geographic proximity situated neighboring markets;…”
mentioning
confidence: 99%